Agriculture and Rural Development Day at the Cancún Climate Change Conference - Otieno, Y. (2010)
Agriculture and Rural Development Day (ARDD) was held for the second time during the Sixteenth Conference of the Parties (COP16) to the United Nations Framework Convention on Climate Change (UNFCCC) which took place earlier this month at Cancún, Mexico. The day-long event, which drew hundreds of participants including policy makers, farmers, scientists and journalists, aimed to put agriculture on this year’s climate change agenda. In her opening speech, Inger Andersen, CGIAR Fund Council Chair and Vice President of Sustainable Development, World Bank talked about the intersection of agricultural development, food security and climate. She proposed agriculture as a solution that was a triple win of increased food security, resilience and reduction of emissions. The success of the World Agroforestry Centre (ICRAF) in promoting the spread of Evergreen Agriculture in Africa was cited as an example of a climate-smart agricultural technique that can both increase crop yields and help to reduce